The role of international trade and industrialization in economic growth in developing countries: The case of Malaysia. - Ahmadi, Seyed Ali. (My University, 1997)
This study found that: a strong, positive and highly significant relationship between exports growth and income growth is observed with high explanatory powers for the models; export growth in Malaysia makes a contribution to income growth over and above the contribution of primary factors of production (labor and capital); introducing export as a variable in the production function will increase the power of the model; the elasticity of income with respect to export was significantly higher than those of other developing countries previously investigated by other researchers.

Data for the empirical estimation of the models came from secondary sources in the statistical publications of World Bank and International Monetary Fund (IMF), or directly from these two institutions. The data covered the period from 1966 to 1994.

The simultaneous-equation model results indicated that: growth of income primarily depended on growth of exports and growth of capital; growth of investment primarily depended on growth of income but was negatively affected by growth of exports; industrialization primarily depended on the export growth; export growth inversely related to the unit price of exports and positively related to the world income and foreign capital inflow; the primary determinant of export growth was the growth of foreign capital inflow.

Several simple regression models tested the hypothesis that the growth of exports or growth of exports and industrialization makes significant contribution to the growth of GPD in Malaysia. These models were estimated with ordinary least squares. Additionally, a simultaneous-equations model of trade, industrialization and economic development was constructed. The model was tested with Full-Information Maximum Likelihood. Growth of income was modeled as a function of the growth of labor (L), capital (I), exports and industrialization (R). The variables investment, industrialization and exports were endogenized and modeled as functions of other endogenous and exogenous variables as follows: growth of I as a function of growth of Y, X and Foreign Capital Inflow (F), growth of R as a function of the growth of Y, X and lag variable for R, and growth of exports as a function of price of exports, world income and growth of Foreign Capital Inflow (F) and investment. The model was estimated by Full Information Maximum Likelihood.

The purpose of this study was to investigate the role of exports and industrialization in the economic development of Malaysia. To achieve its purpose, this study used and tested several models of exports and economic growth.
Keywords: Political Science, International Law and Relations.; Exports Malaysia.; Malaysia Economic policy.; Malaysia Economic conditions.; Industrialization Malaysia.; Malaysia Commerce.; Economics, General.